Perancangan Model Sistem Otomatisasi Pengajuan Angka Kredit Dengan Menggunakan TOGAF Architecture Development Method (Studi Kasus: Badan Pemeriksa Keuangan RI) - , Farian Gustarto Wibowo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
BPK issued regulations on Functional Auditors (JFP) as a step to improve the competence of its Auditors. This step is done to improve the quality of test results in an effort that the State finances are managed in a transparent and accountable. Auditors has a hierarchy and rank are determined based on credit score owned Auditors. Submisiion, assessment, and determination of the number of credit BPK auditors are still using manual system and be done with selfassessment becomes less effective and efficient for examiners to increase the credit. Automation systems filing credit score is very important in helping auditors in credit score calculations apply a more effective and efficient to support continuity and tenure ladder. In order for the system integration to work, it needed a tool or framework, which in this study using the TOGAF ADM. This study focuses on how to design a model system integration applications available as an integrated system that automates the assessment and filing credit score.